Thermophysical and ultrasonic properties of GdCu under the effect of temperature and pressure. (3rd March 2020) - Pandey, Dharmendra Kumar; Yadav, Chandreshvar Prasad
ABSTRACT: The characteristics of heavy rare earth intermetallic GdCu are investigated by the theoretical evaluation of thermophysical and ultrasonic properties at different temperature and pressure. Initially, second-order elastic constants (SOECs) are determined in the temperature range 300–900 K and pressure range 0–40 GPa using the potential model approach. The elastic moduli and anisotropy factor are also estimated for elastic and mechanical characterization. Later on, ultrasonic velocity, thermal conductivity, thermal expansion coefficient and melting point of chosen compounds are calculated utilizing estimated SOECs, density and lattice parameters within the same physical conditions for the ultrasonic and thermal characterization. It is found that the bulk modulus and thermal conductivity enhance with increase in pressure while reduce with temperature. The ultrasonic velocity is found to vary linearly with temperature and non-linearly with pressure. The analysis explores that intermetallic GdCu manufactured at high pressure shall have good mechanical strength, elastic behavior and high melting point.